Linkage Power Europe The EU's Trade Negotiations with China (1975-2019) - Xiaotong, Zhang (Routledge Studies in the Modern World Economy, 2023)
This book looks at the history of the EU's trade negotiations with China from 1975 to 2019 from a distinctive perspective - the EU as a linkage power. The author explains how the EU through linkage strategies speaks with one voice, overcomes its weakness in military capabilities and translates its non-military capabilities into advantages and influences in some specific policy areas. 　 The book systematically traces the European negotiators' tactics in managing the EU's trade relations with China. It's the first time that the history of EU-China trade negotiations is presented to the public by a seasoned trade negotiator. The author, combining the identities of a negotiator and a scholar, gives a panoramic view of EU-China trade relations from 1975, when the European Economic Community established diplomatic relations with China, to 2019 when the Juncker Commission leaves office. This book will appeal to policymakers, think-tankers, professors and students, as well as anyone who is interested in trade policies and negotiations in the EU and China.